Lepidoptera in Rice Ecosystems: Diversity of Stem Borers and Leaf Folders in Karaikal, Puducherry - K. Nishanthini; M. Kandibane (Annals of Agricultural Research, 2025)
Rice, a staple food for billions worldwide, faces numerous threats from insect pests. Among these, stem borers and leaf folders have long been recognized as significant challenges to rice production. A field experiment was executed during Kharif 2019 and Rabi 2019-2020 at Pandit Jawaharlal Nehru College of Agriculture and Research Institute, Karaikal, Puducherry and the species diversity of stem borer and leaf folder species infesting rice was determined. Three different species of rice stem borers, yellow stem borer (Scirpophaga incertulas), pink stem borer (Sesamia inferens), dark-headed striped borer (Chilo polychrysus) and three rice leaf folder species, Cnaphalocrocis medinalis, Marasmia exigua and Marasmia ruralis were identified that were prevalent during the crop season. However, yellow stem borer was dominant over other species of stem borers and showed consistency with a population of 60.71%, and dominantleaf folder species found was C. medinalis(70%).